DESEMPENHO DO TESTE DA HERDABILIDADE UNIVARIADA MEDIANTE DELINEAMENTOS COM DIFERENTES ESTRUTURAS FAMILIARES - RIBEIRO, Alex Oliveira; FERREIRA, Daniel Furtado; SOLER, Júlia Maria Pavan (Brazilian Journal of Biometrics, 2019)
Studies on heritability of quantitave traits are essential for understanding of the genetic contribution of factors associated to diseases, human behavior, among others. For this purpose, designs with families are employed, which make it possible to capture information on the response of interest in specific sets of parents or whole families. In this article, the effect of variation in the structure and size of the families on the performance of the test of univariate heritabilitiy proposed by Blangero et al. (2013) is evaluated through error rates tipo l and the power of the test. The results shown that the test is conservative, independent of the type of family structure employed, the size of the families and the relashionship of kinship between his members. Regarding the power, the results of simulations indicated that the designs with extensive brotherhood led to an increase of the power of the test of heritability. This is due to the greater amount of direct relashionships present in these designs, besides the fact that in the spectral decomposition of the matrix of kinship this design contributes with a major proportion of the eigenvalues lower than 1, which increase the statisc of the test likehood ratio (ELRT).